Modelagem matemática da dinâmica de fluxo rio-aquífero na sub-bacia Patos/ Cariús/ Iguatu no semiárido cearense - Silva, Eldir Bandeira da (2018)
The simulation of the river-aquifer interaction is a dynamic and challenging process, being this process important both in the characterization of the underground water systems and in the sustainability, preservation and development of aquifer systems. With this, the main objective of this work was to characterize the alluvial zone of the region and to understand hydrogeological and hydrodynamic processes responsible for the river-aquifer interaction using mathematical modeling. The study was carried out in the Patos/ Cariús/ Iguatu sub-basin (SBHPCI), located in the Alto Jaguaribe basin, Ceará. The sub-basin has an area of approximately 1,018.9 km2 , drains a stretch of 62.2 km of the Jaguaribe river and presents in its geological structure alluvial aquifers in sedimentary and crystalline environment. The program applied in the flow simulations of the river-aquifer interaction was Visual MODFLOW for Windows, version 2.7. The SBHPCI presents nine pluviometric stations, three fluviometric stations and three wells monitored by Hobo U20 water level sensors (Onset®). Monitoring of the wells occurred from April 2010 to November 2013, with data collected every six hours. The parameters hydraulic conductivity of the aquifer (k), specific production (Sy) and river bed conductance (CRIV) were adjusted in the calibration stage of the model. In this step, the constant loads at the input and output of the system, defined as boundary conditions, were also adjusted. The river basin flow, before and after each event, was adjusted based on the water balance provided by the model. For all the events analyzed, the river-aquifer interaction occurred only through loss in transit, indicating the importance of the river in the recharge of the local aquifer. The hydraulic gradient calculated from the hydraulic loads of the wells was 0.0007 m m-1 . Hydraulic conductivity (k) and the specific production of the aquifer, considered free, homogeneous and isotropic, were estimated by stationary calibration of the model at 4.5 x 10-4 m s -1 and 16% respectively. In general, the model was able to simulate the conditions observed in the field, but it was verified, in order to obtain more robust answers, the need for improvement and maintenance of a monitoring and data collection system in the studied area.